The Impact of Artificial Intelligence Adoption on Productivity and Economic Growth in the Industry 5.0 Era - Alaika Zinatul Hayat (PT. AVID MEDIA INDONESIA, 2026)
The rapid advancement of artificial intelligence (AI) technologies has become a key driver of economic transformation in the Industry 5.0 era, where human–machine collaboration plays a central role in improving efficiency and innovation. AI adoption is increasingly recognized as a strategic factor that enhances productivity and supports sustainable economic growth across various sectors. This study aims to analyze the impact of AI adoption on productivity and economic growth within the framework of Industry 5.0. This research employs a quantitative approach using secondary data obtained from economic databases, industry reports, and statistical publications related to technology adoption and economic performance. Data were collected through documentation techniques and analyzed using descriptive statistics and multiple regression analysis to examine the relationships between AI adoption, productivity indicators, and economic growth. The results indicate that AI adoption has a positive and significant effect on productivity improvement, particularly through enhanced operational efficiency, technological upgrading, and improved workforce performance. Furthermore, productivity improvements resulting from AI adoption contribute significantly to economic growth by increasing industrial output and strengthening competitiveness in the digital economy. In conclusion, AI adoption plays a crucial role in enhancing productivity and supporting economic growth in the Industry 5.0 era. However, maximizing these benefits requires complementary investments in digital infrastructure, workforce skills, and supportive policy frameworks